Believing Happiness Lies Outside in the Digital Age: A Systemic Model of Externality of Happiness, Doomscrolling, Schadenfreude, Family Functioning, and Mental Well-Being - Korun, Ali Berke; Satici, Seydi Ahmet (SPRINGER, 2025)
Components affecting individuals' mental well-being in the digital age are emerging as complex and multi-layered structures, increasing the need for holistic and systemic approaches. This study aims to investigate the relationships between individual, behavioural, emotional, and contextual factors associated with mental well-being in the digital age. Specifically, this study examined whether the externality of happiness predicts mental well-being through the sequential mediating roles of doomscrolling, schadenfreude, and family functioning. This research employed a cross-sectional survey design. The relationships between the externality of happiness, doomscrolling, schadenfreude, family functioning, and mental well-being were analysed using a serial mediation model. Structural equation modelling, central network analysis, and clustering network analysis were employed in a sample of 811 individuals from T & uuml;rkiye. SEM findings reveal that doomscrolling, schadenfreude, and family functioning play a serial mediating role in the relationship between the externality of happiness and mental well-being (chi 2/df = 3.86; CFI = 0.98; TLI = 0.97; SRMR = 0.04; RMSEA = 0.056). According to the results of the central and clustering network analyses, doomscrolling and mental well-being were found to be in the same subsystem, while schadenfreude, the externality of happiness, and family functioning were grouped in another cluster. The findings reveal that individual tendencies interact with digital behaviours and contextual factors in a multidimensional structure. In this respect, the study contributes to the development of holistic mental health models for multifactorial systemic determinants of mental well-being in the digital age and provides practical implications for family-based interventions, digital literacy programs, and counselling practices.
Keywords: Digital age; Doomscrolling; Externality of happiness; Family functioning; Mental well-being; Schadenfreude; SOCIAL MEDIA; STUDENTS; BEHAVIOR; Psychology; Substance Abuse; Psychiatry